PERSAINGAN USAHA DI ANTARA PERUSAHAAN NEGARA, SWASTA, DAN KOPERASI - Indrati Rini (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2002)
Monopolistic activity operated by a few big enterprises in Indonesia has increased unbalanced competition. In the other hand, small companies, state-owned corporations and corporations still face difficulties in grabbing the equal bargaining power. Therefore, production process and distribution channel of goods and services should be developed in a better atmosphere and more competitive way so that enabled the community to get the goods and service in a optimum quality at reasonable price.